Ammonium influences kinetics and structure of methanotrophic consortia. (15th April 2019) - López, Juan C.; Porca, Estefanía; Collins, Gavin; Clifford, Eoghan; Quijano, Guillermo; Muñoz, Raúl
Graphical abstract: Highlights: NH4 + concentrations of 4–80 mM allowed CH4 biodegradation at 4% ( v/v ) CH4 . Microbial diversity decreased concomitantly with an increase in NH4 + levels. Low NH4 + concentrations favoured enrichment of type II methanotrophs. Specific CH4 biodegradation rates were highest at low NH4 + levels. 20–80 mM NH4 + enriched type I methanotrophs and increased microbial affinity for CH4 . Abstract: The literature is conflicted on the influence of ammonium on the kinetics and microbial ecology of methanotrophy. In this study, methanotrophic cultures were enriched, under ammonium concentrations ranging from 0 to 200 mM, from an inoculum comprising leachate and top-cover soil from a landfill. Specific CH4 biodegradation rates were highest (7.8 × 10 −4  ± 6.0 × 10 −5  gCH4  gX −1  h −1 ) in cultures enriched at 4 mM NH4 +, which were mainly dominated by type II methanotrophs belonging to Methylocystis spp. Lower specific CH4 oxidation rates (average values of 1.8–3.6 × 10 −4  gCH4  gX −1  h −1 ) were achieved by cultures enriched at higher NH4 + concentrations (20 and 80 mM), and had higher affinity for CH4 compared to 4 mM enrichments. These lower affinities were attributed to lower diversity dominated by type I methanotrophs, of the Methylosarcina, Methylobacter and Methylomicrobium genera, encountered with increasing concentrations of NH4 + . The study indicates that CH4 oxidation biotechnologies applied at low NH4 + concentrations can support efficient abatement of CH4 and high diversity of methanotrophic consortia, whilst enriching type II methanotrophs.